Modern Guidelines on Benign Prostatic Hyperplasia - Ahmad, Sajjad (Journal of Postgraduate Medical Institute, 2011)
Bengin prostatic hyperplasia (BPH) is closely rleated to urinary symptoms. Mild urinary symptoms are very common in the aging man, and beyond the age of 60 years 40% of men have lower urianry tract symptoms (LUTS). The exact prevalence of symptomatic BPH, however is difficult to determine, because BPH does not always cause urinary symptomas. The prevalence of BPH is increasing because the number of aging males in the population is increasing. Consequently the mdical costs associated with BPH are increasing as well. The guidelines developed under the sponsorship of the world health organization were among the first to provide definitions and recommendations for the diagnostic evaluation and treatment of men presenting with LUTS caused by BPH. These recommendation are based on a thorough review of the available literature and the global subjective opinion of recognized experts serving on focussed committees.